Introducing Vol. 12 No. 2 - Kim, Min Seong (Sanata Dharma University, 2024)
This editorial introduces the five articles included in Vol. 12 No. 2 of Retorik: Jurnal Ilmu Humaniora. It also includes updates about the journal and outlines its plans for a special volume in the year 2025.